The Study of Exchange Bias Effect in PtxCo1-x/CoO Bilayers - Erkovan, M.; Akoz, M. E.; Parlak, U.; Ozturk, O. (SPRINGER, 2017)
We investigated the exchange bias effect in PtxCo1-x/CoO bilayers as a function of Pt concentration. Chemical analysis on the Pt Co-x(1-x) layer confirmed that x varies from 0.6 to 0.9 by 0.1 step. Hereby, we present magnetic anisotropy measurements as well as magnetic hysteresis measurements at low temperatures. It was found that exchange bias field and blocking temperature values of PtxCo1-x/CoO bilayers strongly depend on Pt concentration. Moreover, we showed that it is possible to obtain a higher exchange bias effect with a less Co content in PtCo alloy layers. Both blocking temperature and exchange bias effect results of the bilayer system were discussed with two different scenarios.
Keywords: Exchange bias effect; PtCo alloy; Blocking temperature; FM/AFM structures; MAGNETIC-CIRCULAR-DICHROISM; ANISOTROPY; IRON; BIOMOLECULES; TEMPERATURE; SENSORS; Physics